Changes in the osmolarity of the embryonic microenvironment induce neural tube defects. Issue 5 (14th April 2015) - Jin, Yi‐mei; Wang, Guang; Zhang, Nuan; Wei, Yi‐fan; Li, Shuai; Chen, You‐peng; Chuai, Manli; Lee, Henry Siu Sum; Hocher, Berthold; Yang, Xuesong
SUMMARY Many maternal disorders that modify the embryonic microenvironment, such as a change in osmolarity, can affect development, but how these changes influence the early embryo remains obscure. Neural tube defects, for example, are common congenital disorders found in fetus and neonates. In this study, we investigated the impact of anisotonic osmolarity (unequal osmotic pressures) on neural tube development in the early chick embryo, finding that neuronal cell differentiation was impaired in the neural tube due to enhanced apoptosis and repressed cell proliferation. Anisotonic osmolarity also affected normal development of the neural crest, which in turn influenced abnormal development of the neural tube. As neural tube development is highly dependent on the proper expression of bone morphogenetic protein 4 (BMP4), paired box 7 (PAX7), and sonic hedgehog (SHH) genes in the dorsal and ventral regions along the tube, we investigated the impact of anisotonic osmolarity on their expression. Indeed, small changes in osmolarity could positively and negatively impact the expression of these regulatory genes, which profoundly affected neural tube development. Thus, both the central and peripheral nervous systems were perturbed by anisotonic consitions as a consequence of the abnormal expression of key genes within the developing neural tube. Mol. Reprod. Dev. 82: 365–376, 2015. © 2015 Wiley Periodicals, Inc.